2010
DOI: 10.1016/j.snb.2009.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and performance of uncoated microcantilever-based chemical sensors

Abstract: To cite this version:Sébastien Tétin, Benjamin Caillard, Francis Ménil, Hélène Debéda, Claude Lucat, et al.. Modeling and performance of uncoated microcantilever-based chemical sensors. Sensors and Actuators B: Chemical, Elsevier, 2010, 143, pp. AbstractChemical sensors based on vibrating silicon microcantilevers without sensitive coating are investigated herein.The sensor signal is the relative variation of the microcantilever resonant frequency which depends on both the viscosity and the density of the fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…The sensitivity to mass density can be approximated by [10] (4) From Eq. (4) one may conclude that the relative frequency shift due to the mass density variation of the gas increases with the ratio of the microcantilever width to the microcantilever thickness.…”
mentioning
confidence: 99%
“…The sensitivity to mass density can be approximated by [10] (4) From Eq. (4) one may conclude that the relative frequency shift due to the mass density variation of the gas increases with the ratio of the microcantilever width to the microcantilever thickness.…”
mentioning
confidence: 99%
“…The Euler-Bernoulli equation taking into account the hydrodynamic force acting on the uncoated microcantilever is commonly used to model the behavior of resonating microcantilevers in fluid media when the influence of the beam's shearing deformation and rotational inertia can be neglected [8] and [12]. Fig.…”
Section: Modelingmentioning
confidence: 99%
“…For chemical and biochemical sensing applications, the microcantilevers are usually coated with a sensitive layer whose purpose is to selectively sorb the analyte of interest, resulting in either a static deflection (bilayer effect) in the static mode or a shift in the resonant frequency (mass effect) in the dynamic flexural mode. Furthermore, it has been demonstrated that uncoated micro-or millimeter size cantilevers operated in the dynamic flexural mode exhibit good sensitivities to gas mass density [7,8], liquid mass density [9] and/or viscosity [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] Masses in the range of picograms and femtograms have been detected using these devices, with projected detection limits on the order of attograms. [11][12][13] While dynamically driven microcantilever chemical sensors are well suited for gas-phase detection, [1][2][3][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21] their usefulness as a sensing platform is limited when operating in viscous liquid media. 7,[22][23][24][25][26][27][28][29] Due to the additional fluid resistance (combined effects of fluidrelated inertial and viscous forces), the beam's resonant frequency, f res , and quality factor, Q, will drastically decrease when the operating medium is changed from air to liquid; 22,28,[30][31][32] these decreases are due to the increases in the f...…”
Section: Introductionmentioning
confidence: 99%